Dangerous Trends in Law Making in India. (11th October 2016) - Chaturvedi, Kameshwar Nath
Abstract: Dangerous legislative trends are emerging that threaten the effective protection of the rule of law. In India, the role of parliamentarians is being diluted in a number of ways. The role of the Upper House of Indian Parliament (Rajya sabha) in law making, is diluted, by inclusion of non-tax laws in the Finance Bill, and by labeling apparently a non-money bill as a money bill. It seems that in order to get its key legislative proposals enacted as law the government rushed through many amendments in non-tax laws through the route of Finance bill. It also succeeded in getting enacted Aadhar Act as a money bill though apparently Aadhar Act falls in the category of a financial bill. The Constitution of India and parliamentary procedure allows Rajya Sabha to effectively debate and vote on a financial bill. A Money Bill can be introduced only in the Lok Sabha. A Money Bill after being passed by the Lok Sabha is transmitted to the Rajya Sabha. It is the discretion of the Lok Sabha to accept or reject the amendments made by the Rajya Sabha to a money bill. The Aadhar Act, 2016 could have been introduced as a financial bill as its predecessor the National Identification Authority of India bill, 2010 was rightly treated a financial bill.